Ambient CO2 adsorption using coconut shell activated carbon: study on the optimization of the chemical activation conditions using response surface methodology (RSM), isotherms and thermodynamics / Nur Afiqah Anuwar - Anuwar, Nur Afiqah (2022)
The development of activated carbon from biomass precursors to adsorb CO2 from various sources of emission is challenging since numerous factors affect the adsorption capacity, including the chemical activation parameters chosen. There is a shortage of comprehensive data on optimizing chemical activation parameters to modify the surface properties of activated carbon utilizing Response Surface Methodology (RSM) and discussing the interaction between the activation conditions and the pore properties produced.